Lesions of the breast with uncertain malignant potential - I. V. Vуsotskaya; I. A. Gladilina; V. Yu. Kirsanov; N. V. Ponedelnikova; E. A. Kim; V. E. Ponomarev (ABV-press, 2021)
The article deals with a peculiar group of breast diseases, which belongs to the B3 category according to the BI-RADS classification, the so-called lesions with undefined malignant potential. The basic information concerning their biological behavior and modern tactical approaches to the management of patients with similar changes in the mammary gland are presented. The possibility of conservative management, as well as the minimization of surgical aid, in cases of indications for it, up to vacuum aspiration biopsy is being considered. In addition, the significance of these diseases for the subsequent development of pre-invasive and infiltrative cancer is discussed.